Cultural Orientation of Self-Bias in Perceptual Matching - Jiang, Mengyin (Front Psychol, 2019)
Previous research on cross-culture comparisons found that Western cultures tend to value independence and the self is construed as an autonomous individual, while Eastern cultures value interdependence and self-identity is perceived as embedded among friends and family members (Markus and Kitayama, 1991). The present experiment explored these cultural differences in the context of a paradigm developed by Sui et al. (2012), which found a bias toward the processing of self-relevant information using perceptual matching tasks. In this task, each neutral shape (i.e., triangle, circle, square) is associated with a person (i.e., self, friend, stranger), and faster and more accurate responses were found to formerly neutral stimuli tagged to the self compared to stimuli tagged to non-self. With this paradigm, the current study examined cross-cultural differences in the self-bias effect between participants from Hong Kong and the United Kingdom. Results demonstrated a reliable self-bias effect across groups consistent with previous studies. Importantly, a variation was identified in a larger self-bias toward stranger-associated stimuli in the United Kingdom participants than the Hong Kong participants. This suggested the cultural modulation of the self-bias effect in perceptual matching.